Elsberg Syndrome with Mixed Presentation as Meningitis Retention Syndrome: A Pediatric Case Report and Comprehensive Review of the Literature - Mandy Hsu; Nader El Seblani; Zahra Zhu; Bhuvaneswari Ramisetty; Christopher Day; Jikku Zachariah; Divpreet Kaur; Ashutosh Kumar; Sita Paudel; Dustin Paul; Puneet Singh Kochar; Paul R Carney; et al. (MDPI AG, 2023)
Elsberg syndrome is a typically infectious syndrome that may cause acute or subacute bilateral lumbosacral radiculitis and sometimes lower spinal cord myelitis. Patients often present with various neurological symptoms involving the lower extremities, including numbness, weakness, and urinary disturbances such as retention. A 9-year-old girl with no significant past medical history presented with altered mental status, fever, urinary retention, and anuria and was found to have encephalomyelitis. An extensive diagnostic workup led to ruling out possible etiologies until identifying Elsberg syndrome. In this report, we describe a case of Elsberg syndrome caused by West Nile virus (WNV). To the best of our knowledge, this is the first reported case of its kind in the pediatric population. Utilizing PubMed and Web of Science databases, we reviewed the literature to describe the neurogenic control of the urinary system in correlation to a multitude of neurologic pathologies.